Penerapan Swedish Massage untuk Menurunkan Tekanan Darah pada Lansia Hipertensi di Kelurahan Mojosongo Kota Surakarta - Ridwan Fajar Prasetyo; Eska Dwi Prajayanti (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Background: The prevalence of elderly hypertension in the world according to World Health Orgaization data there are approximately 972 million people or 26.4, which is likely to continue to increase in 2025 to as much as 29.2%. The prevalence rate in Surakarta City, Jebres sub-district is 23,398 people, Mojosongo village is the first with a prevalence of hypertension incidence of 12,296 patients. The development of complementary medicine has a very rapid percentage increase. Globally, complementary therapy to reduce blood pressure has been widely practised, for example Swedish massage. Objective: Describe the results of the implementation of Swedish massage therapy in elderly patients with hypertension in the Mojosongo urban area of Surakarta City. Method: This study used a descriptive research design with a case study approach by observing blood pressure in 2 elderly respondents, carried out 1x a day for 3 meetings in 1 week with a time of 20-30 minutes in 1 session. The instruments used are observation sheets, Blood Pressure Monitors, and SOP sheets. Results: There is a decrease in blood pressure after giving swedish massage therapy to Mr T. T and Mr. S from grade 1 hypertension to prehypertension. Conclusion: The application of swedish massage therapy can reduce blood pressure in the elderly with hypertension in both respondents.